Mobile Commerce untuk Sales Order dan Tracking Order berbasis MVC - Andi Leo; Verri Kuswanto; Lily Damayanti (ALGOR, 2022)
Internet has become one of the important needs in everyday life. Internet access is very easy with various types of devices, one of which is mobile. This opens up opportunities for business people to serve customers in carrying out mobile-based transactions or what is called m-commerce. M-Commerce provides new innovations in the business world with the convenience it offers, making it used for new business breakthroughs, one of which is delivery service as a service that pampers buyers so they don't have to wait for goods or services ordered for days. This M-Commerce application for purchasing products or ordering services is built using the angularJS method based on the Model View Controller (MVC). This makes the software development cycle more streamlined and easy. This application provides easy service to m-commerce users because of the addition of delivery service, it is also expected to increase the purchase of goods or services on a regular basis. The conveniences obtained from this application are in the form of ordering goods which will then be delivered by the courier, tracking the courier's position while in the process of ordering, selecting products and services that are easier for users to see and viewing transactions and user history, on a mobile basis.